Implications of child-friendly school policies in reducing cases of violence against children in elementary schools - Bambang Saptono (Jurnal Prima Edukasia, 2022)
The purpose of this study was to analyze the impact of implementing child-friendly school policies in elementary schools. This research is quantitative research with survey design. Observations on the implementation of the policy were made to several schools in the Kulon Progo area. Analysis of field data regarding cases of child violence was carried out through descriptive statistics and literature review as a description of the condition of child-friendly schools in Indonesia. The results of the study indicate that the implementation of child-friendly school policies in the Kulon Progo Region is in the quite appropriate category. It is necessary to take steps in optimizing the applicable child-friendly school policy model. The constraint factors in implementing child-friendly school policies still need special attention, especially for education providers and the government.